Female entrepreneurship in Asia: a critical review and future directions - Sonja Franzke; Jie Wu; Fabian Jintae Froese; Zi Xuan Chan (Asian Business & Management, 2022)
Female entrepreneurs contribute substantially to economic growth in Asia. Despite their economic success, we know relatively little about them. This article presents a comprehensive review of female entrepreneurs in Asia, focusing on how they differ from their counterparts in the West, along four dimensions: female entrepreneurs' unique characteristics, their distinct intentions, their constraints on resources, and their management styles. Our analysis revealed striking differences between female entrepreneurs in Asia and those in the West but also substantial heterogeneity within Asia. In developing Asian countries, female entrepreneurs often have a low level of education and work in the informal sector, driven by economic necessity, whereas many female entrepreneurs in transitioning/developed Asian countries are highly educated and work in high-growth industries. Culture and different religions, e.g., Islam and Hinduism, are major sources of constraints for the education and financing of female entrepreneurs in Asia. Family ties play a key role in the leadership style of female entrepreneurs in Asia. The review and analysis have important implications for future research and entrepreneurial practice.
Keywords: 650; Female entrepreneurship; Cultural values; Religion; Entrepreneurial intention; Leadership; Asia